EKSISTENSI KALENDER BALI DALAM PENENTUAN HARI BAIK DI DESA ADAT SELULUNG, KECAMATAN KINTAMANI, KABUPATEN BANGLI - I Nyoman Ranem; I Nengah Arimbawa (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2026)
The Balinese calendar is the essence of the teachings of wariga which is used as an initial guideline to facilitate calculating days, wuku, tanggal panglong, śaśih, pratiti and ala ayuning padewasaan. The choice of auspicious days for an activity is determined based on a combination of good bad calculations obtained from the Balinese calendar with reference to primary sources, namely the core wariga texts owned by paniwak dewasa (wariga practitioners). This study uses a qualitative research type. The research location in this study is located in Selulung Traditional Village, Kintamani District, Bangli Regency. The technique for determining informants uses a purposive sampling technique. The instrument in this study is the researcher himself with research tools such as interview guidelines, notes, recording devices (cellphones), and cameras. Data collection techniques are carried out through observation, in-depth interviews, documentation studies, and literature studies. Data analysis techniques are carried out through the stages of data collection, data reduction, data presentation, and data processing which ends with verification and proof. The results of the study show that determining a good day for an activity uses the Balinese Calendar as an initial guideline to make it easier to determine the day, wuku, tanggal panglong, śaśih, pratiti and the calculation of good and bad padewasaan, while determining a good day for an activity is always based on the core wariga text owned by the paniwak dewasa.